The history of the Jewish church - Stanley, Arthur Penrhyn 1815-1881; Princeton Theological Seminary (New York C. Scribner's sons, 1879)
I. Abraham to Samuel.--II. From Samuel to the captivity.--III. From the captivity to the Christian era.
First published under title: Lectures on the history of the Jewish church. - Contains bibliographical references
Keywords: Jews -- History -- To A.D. 70; Judaism